Amnestia w polskim prawie karnym - Krajewski, Radosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
Amnesty is a collective pardon law whereby state authorities remit or reduce the punishment of certain groups of offenders. In the recent history of Polish criminal law, amnesties were also an instrument used against actual or alleged political opponents, which was part of the formula of an authoritarian or totalitarian state. The number of amnesties in the interwar and postwar periods in Poland was similar, but their motives were different. Amnesty was announced for the last time in 1989, and it is assessed differently by representatives of legal science. The aim of the article is to refer to these views, and above all to catalogue individual amnesty acts and to assess amnesty as an instrument of criminal law.
Keywords: amnestia; przestępstwo; prawo karne; polityka karna; autorytaryzm